Investigation of Factors Influencing on Ammonia Emission from Soils in Agricultural Land - Gun-Yeob Kim; Yeon-Jin Lee; Eun-Ji Cho; Jae-In Lee; Eun-Chae Im; Hancheol Hwang; Sang-Yoon Kim; Sung-Chang Hong; Jin-Ho Kim; Seong-Jik Park (대한환경공학회지, 2022)
Objectives Major factors affecting ammonia emission from the soil and strategies to reduce ammonia emission were investigated through literature surveys. Methods An academic search was conducted using keywords such as agriculture, ammonia, and fine dust, and the effects of soil characteristics on ammonia emission were summarized for each factor. Results and Discussion Emissions of ammonia into the atmosphere can reduce economic returns for a farmer and negatively impact the atmospheric environment by acting as a precursor to PM2.5 formations. It is reported that agriculture accounts for 78% of the total ammonia emission sources in Korea. Ammonia emission from the soil is affected by the type of ammonia fertilizer, soil moisture, pH, temperature, cation exchange capacity, organic matter, and soil texture. An increase in soil moisture increases ammonia emissions. As soil pH increases, ammonia emissions increase, noticeably above 7.5. An increase in soil temperature increases the rate of hydrolysis of urea and the rate of conversion to ammonia gas, resulting in increased ammonia emissions. Soils with high cation exchange capacity adsorb ammonium to reduce ammonia emissions. Soils with a high clay content and soil organic matter content are more buffered to changes in soil pH, reducing ammonia emissions. Conclusion Based on understanding the mechanisms and causes of ammonia emission from the soil, it is possible to establish soil and environmental management to reduce ammonia emissions into the atmosphere.